DETERMINATION OF EMPLOYABILITY SKILLS REQUIRED BY ELECTRICAL TECHNOLOGY STUDENTS IN COLLEGES OF EDUCATION IN NIGERIA - Sunday Rufus Olojuolawe; Fadila Nor Bt Amin (Universitas Diponegoro, 2019)
The rate of unemployment among youths in Nigeria has assumed a worrisome dimension. More importantly that those affected are specialized graduates from tertiary institutions. The youth unemployment rate has been of persitent increase since 2014 from from 11.7% to 36.5% in 2018. It has been established that the vacancies exists, but the graduates lack the skills to match the jobs. Therefore, the aim of this paper was to identify the constructs and sub-constructs of employability skills that are needed to match Electrical Technology students with the labour market. The resaerch design is a qualitative metthod involving document analysis and interview protocol of stakeholders in electrical technology. The stakehoders were the academics and the employers. The documents were analysed using frequency matrix table. While the interview of the stakeholders (experts) were done thematically. To ensure the reliability of the constructs and sub-constructs, an item pool was constructed to determine the agreement and content reliability index for the constructs. From the item pool, 5 constructs and 193 sub-constructs were generated. These were constructed into instrument for expert review. Three experts in electrical technology rated the instrument for determining the aggreement level, using the Fleiss kappa approach. The percent agreement for the raters are 89.63%, 86.01%, and 81.86% respectively with a mean agreement of 85.83%. The 85.83% indicate an almost perfect agreement by the experts for each of the constructs in the instrument. This is very good for producing a functional framework of employability skills.